2009
DOI: 10.3168/jds.2008-1716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary forage to concentrate ratio on volatile fatty acid absorption and the expression of genes related to volatile fatty acid absorption and metabolism in ruminal tissue

Abstract: The objective of the study was to investigate the fractional rate of volatile fatty acid (VFA) absorption and the expression of genes encoding for transporters and enzymes involved in the absorption and metabolism of VFA in ruminal tissue when cattle were fed high or low concentrate diets. Twelve ruminally cannulated Holstein cows were used in a randomized complete block design. The low concentrate (LC) and high concentrate (HC) diets contained 8 and 64% dietary concentrate (dry matter basis), respectively. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
155
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(179 citation statements)
references
References 31 publications
20
155
2
2
Order By: Relevance
“…The response of the ruminal epithelium to an increase of energy (and protein) has been previously studied in sheep, cattle, and goats (19,47,55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The response of the ruminal epithelium to an increase of energy (and protein) has been previously studied in sheep, cattle, and goats (19,47,55).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, supplementation of forage-fed ruminants with sufficient amounts of energy and protein is necessary and significantly improves milk production or daily weight gain (41), but, particularly, a surplus of easily fermented carbohydrates or low-fiber intake will place the animals at risk. Such a change in the diet is a challenge for rumen microbes (31) and especially for the ruminal epithelium with respect to adaptation to the new fermentation pattern (47,55). Insufficient adaptation to diet may result in disintegration of the epithelium (22), translocation of lipopolysaccharides (30), and disturbed transport mechanisms (22) and can further cause subacute ruminal acidosis (14, 49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, rumen availability and degradability of grain starch can be increased by processing grain (Hale, 1973;Theurer, 1986). Previous studies have shown that the feeding of grain-based diets decreases rumen pH (Yang and Beauchemin, 2007;Penner et al, 2009). In most studies, rumen pH measurements were generally taken either once (Tajima et al, 2001), twice (Abughazaleh et al, 2003;Mohammed et al, 2009), four times (Klieve et al, 2003) or six times a day (Kalscheur et al, 1997;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of diet that contains high proportion of NFC possibly led to an increase in VFA production. Penner et al (2009) illustrated that production of VFA especially propionic acid can be induced by concentrate supplementation. Dehority (2003) also stated that supplying of NFC is able to stimulate VFA synthesis particularly propionic acid.…”
Section: Resultsmentioning
confidence: 99%